Cities on the Prowl - Campbell, Tim (2012)
Cities in the modern world are beginning to share some features with the city-states of millennia past. Now, as then, cities are important, even critical, to economic development. Unlike the walled cities that harbored flourishing trade in medieval Europe, today, cities by the thousands all around the world are looking outward in search not of silk and spices, but rather sources of finance, global talent, and most of all, good ideas. But the search for knowledge isn't always easy.